C(sp3)18F Bond Formation by Transition‐Metal‐Based [18F]Fluorination. Issue 43 (22nd September 2014) - Liang, Steven H.; Vasdev, Neil
<x xml:space="preserve">Abstract</x> Without a trace? Recent advances in aliphatic radiofluorinations enabled by transition metals, specifically cobalt/salen and manganese/salen complexes, have been unveiled. These new approaches operate in a unique way which obviates the need for highly activated substrates for radiolabeling and offers a new synthetic strategy to prepare 18F‐labeled radiotracers.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>